2019
DOI: 10.1109/tcad.2018.2834397
|View full text |Cite
|
Sign up to set email alerts
|

An Energy-Efficient Integrated Programmable Array Accelerator and Compilation Flow for Near-Sensor Ultralow Power Processing

Abstract: In this paper we give a fresh look to Coarse Grained Reconfigurable Arrays (CGRAs) as ultra-low power accelerators for near-sensor processing. We present a general-purpose Integrated Programmable-Array accelerator (IPA) exploiting a novel architecture, execution model, and compilation flow for application mapping that can handle kernels containing complex control flow, without the significant energy overhead incurred by state of the art predication approaches. To optimize the performance and energy efficiency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
2

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Comparing with the CPU, the context aware mapping achieves an average of 14× (with a maximum of 23× and minimum of 5×) energy gain. In [1], it is reported that the basic mapping approach combined with the target CGRA with HOM64 configuration achieves leadingedge energy efficiency, surpassing by more than one order of magnitude other state of the art architectures.…”
Section: Area and Energy Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Comparing with the CPU, the context aware mapping achieves an average of 14× (with a maximum of 23× and minimum of 5×) energy gain. In [1], it is reported that the basic mapping approach combined with the target CGRA with HOM64 configuration achieves leadingedge energy efficiency, surpassing by more than one order of magnitude other state of the art architectures.…”
Section: Area and Energy Resultsmentioning
confidence: 99%
“…The article [1] describes an efficient solution for the basic mapping problem. The basic approach takes the CGRA TEDG and CDFG as the inputs.…”
Section: B Solution For the Basic Mapping Problemmentioning
confidence: 99%
See 3 more Smart Citations